JAVANESE FARMERS IN KOTARAYA VILLAGE - Aldi Kurniawan; Windayanti; Juraid; Misnah (SOSIOEDUKASI, 2026)
This study aims to describe the arrival process of Javanese farmers in Kotaraya Village through the Indonesian government's transmigration program and to examine the development of agriculture and agricultural tools in the village. Employing a qualitative descriptive approach through observation, in-depth interviews, and documentation, the findings reveal that the arrival of Javanese farmers since 1973 significantly transformed the physical, economic, and social landscape of Kotaraya Village. Previously uncultivated bushland was collectively converted into productive rice fields and structured settlements. Javanese farmers introduced irrigation systems, adaptive cropping patterns, and semi-modern agricultural technologies, facilitating a transition from traditional to more efficient farming methods. The development of agricultural machinery, particularly the shift from animal-drawn plows to tractors and post-harvest machines, has demonstrably enhanced productivity and community welfare. Furthermore, the presence of Javanese transmigrants fostered harmonious cultural acculturation with indigenous communities, wherein Javanese cultural identity remains preserved. This research concludes that the transmigration program served as a catalyst for agricultural transformation and sustainable social integration in Kotaraya Village..